2000
DOI: 10.1021/ie000326g
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of Hydrocarbons through Partial Oxidation in Supercritical Water

Abstract: We propose a new process for the hydrotreatment of heavy oils in supercritical water (SCW). The discussion in this paper is composed of three parts:  (1) hydrogenation through water-gas shift reaction in supercritical water, (2) selective formation of carbon monoxide by partial oxidation in supercritical water and through combinations of these two, and (3) hydrogenation of hydrocarbons through their partial oxidation in supercritical water. In the experiments involving hydrogenation of dibenzothiophene, carbaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 16 publications
2
42
1
Order By: Relevance
“…The technique of SCWO is well known, not only because of the destruction of hazardous organic materials into CO2 and H2O [82,83], but also because hydrogenation can proceed without the supply of additional molecular hydrogen [84,85]. In SCW, CO, forming the partial oxidation of hydrocarbon, will undergo a WGS reaction to form in situ hydrogen [85].…”
Section: Partial Scwomentioning
confidence: 99%
See 1 more Smart Citation
“…The technique of SCWO is well known, not only because of the destruction of hazardous organic materials into CO2 and H2O [82,83], but also because hydrogenation can proceed without the supply of additional molecular hydrogen [84,85]. In SCW, CO, forming the partial oxidation of hydrocarbon, will undergo a WGS reaction to form in situ hydrogen [85].…”
Section: Partial Scwomentioning
confidence: 99%
“…The partial SCWO of some model hydrocarbon compounds [84][85][86][87][88][89][90][91] and asphalt [59] showed that the in situ hydrogen is more active than molecular hydrogen in the case of the hydrogenation of hydrocarbon. Sato et al [42] reported the effects of reaction temperature, water/oil ratio, and air pressure as an oxygen source, on the formation of coke.…”
Section: Partial Scwomentioning
confidence: 99%
“…First, partial oxidation of hydrocarbons formed aldehyde and ketone, which then decomposed to form CO. In the case of partial oxidation of hexylbenzene at 673 K, the selectivity of CO also tended to increase with increasing water density 5), 6) , similar to the partial oxidation of n-hexadecane. The partial oxidation of methane in SCW using a temperature-controlled flow type reactor was examined using O2/CH4 molar ratio of 0.03 at 673 K under 20 to 30 MPa that corresponded to water density of 0.1 to 0.47 g/cm 3 8) .…”
Section: Partial Oxidation Of Hydrocarbonsmentioning
confidence: 80%
“…The hydrogenation of dibenzothiophene 5) , carbazole 6) and naphthalene 6) proceeded with NiMo/Al2O3 in SCW at 673 K in the presence of CO (SCW CO), H2 (SCW H2) , H2 C O2 ( S C W H2 C O2) a n d . Hydrodesulfurization of benzothiophene and dibenzothiophene proceeds in emulsions with dispersed Mo in subcritical and supercritical water.…”
Section: Catalytic Reactionmentioning
confidence: 99%
See 1 more Smart Citation